Birutė Jasiūnaitė. Lietuvių velniavardžiai. Vilnius: Vilniaus universiteto leidykla, 2018. 312 p. ISBN 978-609-07-0090-7 - Konickaja, Jelena; Stundžienė, Bronė (Slavistica Vilnensis, 2020)
Birutė Jasiūnaitė. Lietuvių velniavardžiai. Vilnius: Vilniaus universiteto leidykla, 2018. 312 p. ISBN 978-609-07-0090-7.